Renovascular hypertension in neurofibromatosis. Issue 759 (January 1989) - Pollard, S. G.; Hornick, P.; Macfarlane, R.; Calne, R. Y.
Abstract : We present two patients with renovascular hypertension in association with neurofibromatosis. In both cases the diagnosis was established by angiography. The first patient suffered occlusion of the right renal artery combined with intrarenal arterial lesions. Treatment was by autotransplantation. The second patient suffered bilateral intrarenal arterial lesions alone and was treated medically. In both patients, control of the hypertension was established. We discuss the aetiology of renovascular hypertension in neurofibromatosis and consider its treatment.